2020
DOI: 10.1186/s13052-020-00943-z
|View full text |Cite
|
Sign up to set email alerts
|

Pooled prevalence and determinants of skilled birth attendant delivery in East Africa countries: a multilevel analysis of Demographic and Health Surveys

Abstract: Introduction Skilled health professional assisted delivery is an effective strategy to reduce maternal and newborn mortality. Skilled assistant delivery can prevent about 16–33% of maternal and newborn mortality. Despite the commitments of the government to assure home free delivery, majority of the births in Sub-Saharan Africa are attended by traditional birth attendants. As to our search of the literature, there is limited evidence on the prevalence and determinants of skilled delivery in Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
7
20
0
Order By: Relevance
“…Training helps to create an educated decision for individuals. This result is in line with previous research by Tessema and Tesema [22], Saah et al [23], and Dickson and Amu [14]. The potential reason would be that they are more likely to advise their partners to have health care delivery when women's partners have higher education and are well aware of the danger signs in pregnancy and the need to be accompanied by a trained birth attendant.…”
Section: Discussionsupporting
confidence: 87%
“…Training helps to create an educated decision for individuals. This result is in line with previous research by Tessema and Tesema [22], Saah et al [23], and Dickson and Amu [14]. The potential reason would be that they are more likely to advise their partners to have health care delivery when women's partners have higher education and are well aware of the danger signs in pregnancy and the need to be accompanied by a trained birth attendant.…”
Section: Discussionsupporting
confidence: 87%
“…Further, their husbands’ employment and education status and whether they wanted the pregnancy while pregnant were also considered. These variables were selected based on previous literature from developing countries [ 25 , 29 , 39 , 40 , 43 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional birth attendants (TBA) and deliveries assisted by female family members are still being used especially in remote rural areas. A study of the determinant of SBA delivery in Eastern African countries concluded that maternal age, women and husband education, wealth index, antenatal care visit, multiple gestations, parity, accessing health care, and residence were major determinants of skilled attendant delivery [ 33 ]. Strategies to overcome these barriers, most of which are outlined in several WHO guidelines, have been found to improve maternal and newborn outcomes.…”
Section: Discussionmentioning
confidence: 99%